The Future of Swiss Hydropower: A Review on Drivers and Uncertainties - Michael Barry; Patrick Baur; Ludovic Gaudard; Gianluca Giuliani; Werner Hediger; Franco Romerio; Moritz Schillinger; René Schumann; Gillaume Voegeli; Hannes Weigt (University of Basel, Center of Business and Economics (WWZ), 2015)
Swiss Hydropower (HP) is currently facing a wide range of challenges that have initiated a debate about future prospects and its role within the envisioned energy transition. Building on this debate, this paper provides an overview of the status and prospects of Swiss HP by identifying and evaluating the different drivers and uncertainties that Swiss HP faces. Based on a review and the perceptions held by some of the main Swiss HP stakeholders the two main topics that need to be addressed are the market driven impacts and the political, legal and social aspects. While the market dynamics cannot directly be influenced by Swiss companies or authorities, the regulatory framework can and needs to be adjusted. However, this requires a comprehensive stakeholder process and is at least a medium-term process.
Keywords: 330; Switzerland; energy transition; hydro power; climate change; electricity market